Factors influencing the signal sensitivity in searches for Z' → ThadThad at √s = TeV with the ATLAS detector - Hsu, Catherine (My University, 2015)
The Z' gauge boson is a hypothetical neutral particle of spin-1 appearing in many theories beyond the Standard Model. In the context of the Z' boson of the Sequential Standard Model in the hadronic decay channel Z' ThadThad, this project investigates improving the sensitivity of the analysis. It is important in the analysis to have high signal e ciency and to be able to distinguish against background processes, thus this project begins with an investigation into new triggers and their combinations that aim to improve the signal e ciency, followed by a study to improve the tau identi cation using tracking. Monte Carlo samples were compared with the data sample for various cut-based variables to investigate which of the variables o er a good discrimination power against the multijet background. The signi cance of each trigger and trigger combinations are shown, as well as the performance of di erent techniques and ideas used to improve the tau identi cation using tracking. Since it is important in this project to be able to reconstruct a tau lepton from its hadronic decay products, this dissertation takes the opportunity to present preliminary results on the study of the light collection uniformity and response in the crack scintillation counters of the ATLAS hadronic tile calorimeter as part of the contribution towards the detector upgrade.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of requirements for the degree of Master of Science. August 11, 2014.
Keywords: Z bosons.; Detectors.